A Photoacoustic Contrast Nanoagent with a Distinct Spectral Signature for Ovarian Cancer Management. Issue 9 (21st December 2022) - St Lorenz, Anna; Moses, Abraham S.; Mamnoon, Babak; Demessie, Ananiya A.; Park, Youngrong; Singh, Prem; Taratula, Oleh; Taratula, Olena R.
Abstract: Photoacoustic imaging (PAI) has tremendous potential for improving ovarian cancer detection. However, the lack of effective exogenous contrast agents that can improve PAI diagnosis accuracy significantly limits this application. This study presents a novel contrast nanoagent with a specific spectral signature that can be easily distinguished from endogenous chromophores in cancer tissue, allowing for high‐contrast tumor visualization. Constructed as a 40 nm biocompatible polymeric nanoparticle loaded with two naphthalocyanine dyes, this agent is capable of efficient ovarian tumor accumulation after intravenous injection. The developed nanoagent displays a spectral signature with two well‐separated photoacoustic peaks of comparable PA intensities in the near‐infrared (NIR) region at 770 and 860 nm, which remain unaffected in cancer tissue following systemic delivery. In vivo experiments in mice with subcutaneous and intraperitoneal ovarian cancer xenografts validate that this specific spectral signature allows for accurate spectral unmixing of the nanoagent signal from endogenous contrast in cancer tissue, allowing for sensitive noninvasive cancer diagnosis. In addition, this nanoagent can selectively eradicate ovarian cancer tissue with a single dose of photothermal therapy by elevating the intratumoral temperature to ≈49 °C upon exposure to NIR light within the 700–900 nm range. Abstract : A nanoagent with a distinct photoacoustic spectral signature identifies ovarian cancer tumors via photoacoustic imaging and guides the subsequent application of phototherapy.